Enhancing the photochemical reversibility of coumarin-containing polymers by molecular orientation control. Issue 44 (26th October 2022) - Inacker, Sebastian; Kahler, Philipp; Hampp, Norbert
Abstract : With the use of an intramolecular approach and restrictions in the mobility, the reversibility of photoresponsive coumarin dimer-containing polymers was enhanced. Abstract : The cycloaddition and -reversion of coumarin is one of the most prominent examples of reversible photo-driven reactions, which are used in a broad field of applications. By applying different illumination wavelengths, materials' properties can be changed. In nearly all cases, limited reversibility is reported without presenting an explanation or even a solution to this problem. This work is dedicated to gain a deeper understanding of what affects photoreaction reversibility. We have chosen a simple polymer architecture based on poly (methyl methacrylate) (PMMA) and an intramolecular coumarin dimer (ICD) to demonstrate that with controlling the molecular orientation of the coumarin moieties by a defined starting configuration and fixation of the coumarin motifs, both cycloreversion and -addition reactions are highly reversible. Loss of the molecular orientation, e.g. by heating, resembles the often-described creeping loss of absorption switching amplitude. Considering the interaction of the coumarin groups' molecular orientation retention and their photo-reversibility, a basis for further advanced applications of coumarin-based materials is provided.